All Days 2007
DOI: 10.2523/iptc-11583-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasonic Technology for Well Leak Detection

Abstract: Identification of the source of pressure communication between well tubing-casing and casing-casing annuli presents an enormous challenge to petroleum engineers. Qatar Petroleum recently field-tested an acoustics based tool to successfully pinpoint the source of high pressure in the tubing casing annulus in a deep gas well in an onshore field. This paper presents a description of the technology and the findings from the field trial. An ultrasonic leak detection tool has been developed for dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The purpose of the method is to detect leaks and identify the place of rupture, which can be detected to an accuracy of inches. Furthermore, it is a sensitive technique (Table 3), because the method can identify micro leaks (previously research, the method has detected leaks of 0.02L/min) [8].…”
Section: Technical Suitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the method is to detect leaks and identify the place of rupture, which can be detected to an accuracy of inches. Furthermore, it is a sensitive technique (Table 3), because the method can identify micro leaks (previously research, the method has detected leaks of 0.02L/min) [8].…”
Section: Technical Suitabilitymentioning
confidence: 99%
“…analyzed. For this, a DSP module is used, which is equipped with a large number of flash RAMs, so it demands a structure that has high processing power, to result in a fully digital signal to be analyzed, and this can be an important restriction for the operation in remote sites [8].…”
Section: Evaluation Of Performances Indicatorsmentioning
confidence: 99%
“…The consequences of gas leaks include the loss of materials and energy, fire and explosion hazards, environmental pollution and decreased production efficiency [ 1 , 2 , 3 , 4 ]. Therefore, it is vital to ensure the tightness of pressure vessels before and during their use; doing so requires a leak location approach to identify any leak holes so that the dangers associated with leakage accidents can be avoided [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic energy analysis is widely used in leak detection because ultrasonic energy propagates through the steel structure of a wellbore [13]. For example, Farooqui et al [14] introduced an acoustic-based tool, Johns et al [15] illustrated an ultrasonic method of leak detection for casing repair, and Johns et al [16] studied the attributes of ultrasound and leaks in Alaskan north slope wells. Other approaches were later based on noise measurement [17] and more recent integrated approaches [18], [19] in which noise and temperature measurements are coupled with a turbine or spinner flowmeter information to correlate data, which are then used to infer the location of leaks.…”
Section: Existing Methods For Leak Detectionmentioning
confidence: 99%
“…[20] extended Farooqui et al's approach [14] by using an array of sensors to capture the acoustic event simultaneously from multiple points. They demonstrated that their method could suppress inaccurate and false echo generated at the leak location as the standing waves from the sound of the leak travel up and down a wellbore.…”
Section: Existing Methods For Leak Detectionmentioning
confidence: 99%